Naming Coffee Shops in Makassar City: Linguistic Landscape Study - Muh. Bahly Basri; Jufri Jufri; Sakaria Sakaria; Iin Nur Yasinta (Balai Bahasa Sulawesi Selatan, 2026)
This study aimed to describe language contestation in naming coffee shops in Makassar City. This study used a qualitative approach with a descriptive design. Data collected by photographing data objects using a device by tracing along the streets of Makassar City and digital space via Google Maps. Data analysis was carried out through the stages of scanning the photos into an Excel data matrix, classification based on language contestation patterns, frequency calculations, pattern interpretation, and drawing conclusions. The research results show that in the monolingual domain, English occupies the most dominant position (52.94%), followed by Indonesian (43.13%), while Makassarese and Turkish each appear in only one shop name (1.96%). In the bilingual domain, the Indonesian–English combination is the most frequently used pattern (78.26%), followed by Indonesia–Makassar (17.39%) and Makassar–English (4.34%) patterns. This finding shows that coffee shop owners in Makassar City tend to use English as a representation of urban areas. The implications of the findings of this research are as a basis for formulating policies for local governments to increase the visibility of local languages in public spaces. AbstrakPenelitian ini bertujuan mendeskripsikan kontestasi bahasa dalam penamaan kedai kopi di Kota Makassar. Penelitian ini menggunakan pendekatan kualitatif dengan desain deskriptif. Pengumpulan data melalui pemotretan objek data menggunakan gawai dengan menelusuri sepanjang jalan Kota Makassar dan ruang digital melalui google maps. Analisis data dilakukan melalui tahapan pemindaian hasil potretan ke dalam matriks data excel, klasifikasi berdasarkan pola kontestasi bahasa, penghitungan frekuensi, interpretasi pola, dan penarikan simpulan. Hasil penelitian menunjukkan bahwa pada ranah monolingual bahasa Inggris menempati posisi paling dominan (52,94%), disusul bahasa Indonesia (43,13%), sedangkan bahasa Makassar dan bahasa Turki masing-masing hanya muncul pada satu nama kedai (1,96%). Pada ranah bilingual, kombinasi Indonesia–Inggris merupakan pola yang paling banyak digunakan (78,26%), diikuti Indonesia–Makassar (17,39%) dan Makassar–Inggris (4,34%). Temuan ini menunjukkan bahwa pemilik kedai kopi cenderung menggunakan bahasa Inggris di Kota Makassar sebagai representasi wilayah urban. Implikasi temuan penelitian ini yaitu sebagai dasar perumusan kebijakan kepada pemerintah daerah untuk meningkatkan visibilitas bahasa lokal di ruang publik.